2021
DOI: 10.3390/ani11010108
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of the Effects of Polyphenols from Chestnut Involucre on Methane Production, Volatile Fatty Acids, and Ammonia Concentration during In Vitro Rumen Fermentation

Abstract: Nutritional strategies can be employed to mitigate greenhouse emissions from ruminants. This article investigates the effects of polyphenols extracted from the involucres of Castanea mollissima Blume (PICB) on in vitro rumen fermentation. Three healthy Angus bulls (350 ± 50 kg), with permanent rumen fistula, were used as the donors of rumen fluids. A basic diet was supplemented with five doses of PICB (0%–0.5% dry matter (DM)), replicated thrice for each dose. Volatile fatty acids (VFAs), ammonia nitrogen conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…These are attributable to the ecological microbiota community, which is, in turn, affected by different factors, such as animal age, breeding system, and diet and feeding technique. The effects of common beech are not available in the literature, even if plants such as Quercus robur L. [ 41 , 42 ] and Castanea sativa L. [ 43 , 44 ], both belonging to the Fagaceae family, were investigated. Odeyinka et al [ 45 ] reported the effects of twelve Scottish plants, including the leaves of F. sylvatica L., on rumen fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…These are attributable to the ecological microbiota community, which is, in turn, affected by different factors, such as animal age, breeding system, and diet and feeding technique. The effects of common beech are not available in the literature, even if plants such as Quercus robur L. [ 41 , 42 ] and Castanea sativa L. [ 43 , 44 ], both belonging to the Fagaceae family, were investigated. Odeyinka et al [ 45 ] reported the effects of twelve Scottish plants, including the leaves of F. sylvatica L., on rumen fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of literature for condensed tannins (CTs) is extensive, whereas hydrolysable tannins (HTs) have been less extensively explored in animal nutrition, even if little attention is given to the chemical composition of the treated extracts. Data about the rumen fermentation effects of Castanea sativa extracts leaf and/or only leaves are scarce [42]; however, different studies reported the effects of chestnut involucre or tannin wood extracts on ruminal fermentation [13,[43][44][45].…”
Section: Effects Of Chestnut Leaf Alcoholic Extract and Its Fractions...mentioning
confidence: 99%
“…Exploiting all the non-edible components of the chestnut, including the leaves, enables the production of quality products [11] with a sustainable reduction in environmental pollution in a circular economy scenario. One of the most promising applications is the recovery of forest biomass and chestnut waste (e.g., leaves, shells, burs) for the optimization of feed ingredients as a strategy to achieve sustainable animal production [12,13]. The growing demand for animal products has led to the adoption of intensive production systems that could compromise animal health, affecting the metabolic status and immunological systems of animals.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the pH values for each group differed from d 0 to 60, falling within the typical range for optimal rumen function in ruminants (6.2–7.2) [ 23 ]. Wang et al [ 24 ] and Ban et al [ 25 ] obtained similar results in in-vitro fermentation and in goats, respectively. Moreover, the rumen NH 3 -N range in this study (14.59–16.06 mg/dL) was within the suitable range for rumen microbial development (3.5–25 mg/dL) [ 26 ].…”
Section: Discussionmentioning
confidence: 61%